Inclusions in Stainless Steels − A Review. Issue 12 (3rd August 2017) - Park, Joo Hyun; Kang, Youngjo
Abstract : Due to its superior features compared to plain steel products, stainless steel has been widely used for various applications, since it is commercialized in the beginning of the 1900's. Since stainless steel is characterized by high chromium (and nickel) content, stainless steelmaking processes have been developed differently to those of ordinary steelmaking. However, like plain carbon steels, non‐metallic inclusions significantly influence the quality of stainless steel products. In order to gain a better understanding of the impact of inclusions on the characteristics of stainless steel products, information from a large amount of previous research on non‐metallic inclusions in stainless steel is reviewed. As expected, non‐metallic inclusions are a probable cause of pitting corrosion, as well as crack initiation and growth. The formation and origin of inclusions during the steelmaking and continuous casting processes are also discussed based on a number of relevant studies. Abstract : In order to gain a better understanding of the impact of non‐metallic inclusions (NMIs) on the characteristics of stainless steel products, information from a large amount of previous research on NMIs in stainless steel is reviewed. NMIs are a probable cause of pitting corrosion, as well as crack initiation and growth. The formation and origin of inclusions during steelmaking and continuous casting processes are also discussed.